Audience Reception Analysis of Hasto Kristiyanto News Coverage in Online Media - Haidar Abdurrohman; Aminah Swarnawati; Harmonis; Tria Patrianti (Ikatan Sarjana Komunikasi Indonesia, 2026)
The designation of Hasto Kristiyanto as a suspect by the KPK triggered political communication dynamics in the digital space that demonstrated how audiences interpret media coverage diversely based on their ideological positions. This research aims to identify media message construction through Pan and Kosicki's framing analysis, analyze factors influencing audience decoding processes, and identify dominant, negotiated, and oppositional patterns in audience reception of Hasto Kristiyanto news coverage in Tempo.co and Kompas.com distributed through X and Instagram platforms from February 1 to June 30, 2025. The study employs a qualitative approach using netnographic methods and content analysis based on Stuart Hall's (1980) encoding/decoding theory and Pan and Kosicki's framing analysis, with data collected through digital observation of 2,139 comments, content documentation, and in-depth interviews with 7 key informants. Research findings reveal that Kompas.com employs procedural-neutral framing focusing on legal aspects while Tempo.co applies critical framing emphasizing power conflicts, audience reception is divided into three decoding positions namely dominant (597), negotiated (579), and oppositional (566), with platform X encouraging negotiated decoding through debate culture while Instagram reinforces oppositional decoding through emotional visual content, influenced by factors of political affiliation, media literacy, collective experiences regarding corruption issues, and digital platform characteristics within the context of power relations and society's ideological structures.